P269 Responsible pathogens of paediatric implantable long term catheter related blood stream infections and effectiveness of antibiotic lock therapy. (6th June 2017) - Kara, Tuğçe Tural; Özdemir, Halil; Erat, Tuğba; Yahşi, Aysun; Aysev, Ahmet Derya; Taçyildiz, Nurdan; Ünal, Emel; Ileri, Dilber Talia; Ince, Elif; Haskoloğlu, Šule; Çiftçi, Ergin; Ince, Erdal
Abstract : Background: Catheter related blood stream infections (CRBSIs) are important problem in paediatric haematology, oncology and immunology patients with central venous catheter. This study aimed to determine incidence of CRBSIs, responsible pathogens and outcomes of antibiotic lock treatment (ALT) in paediatric patients. Methods: Between January 2010 and November 2015 all hospitalised paediatric haematology, oncology and immunology patients who were diagnosed as CRBSIs, were retrospectively included in this study. Causative microorganisms and their antibiotic susceptibility, success rate of ALT, treatment failure, recurrence, catheter removal, complications and mortality are analysed. Results: Seventy eight CRBSIs episodes were detected in 60 paediatric patients. The median age was 106.4±66.6 (86, 3–240) months. Male/female ratio was 1.9/1. The incidence of CRBSIs was 4.20/1000 catheter days. Most frequently detected pathogen was methicillin-resistant coagulase-negative Staphylococcus . Antibiotic lock therapy was administered in 42 patients. Success rate of ALT was 81% (34/42). Catheter was removed without ALT in 36 episodes. Common reasons for catheter removal were sepsis and causative microorganisms which had high probability of biofilm formation. Relapse was observed in 1 (1.3%) episodes and mortality was detected in 3 (3.8%) episodes. Conclusion: Catheter related blood stream infections are important cause of morbidity and mortality in paediatric patients. However, incidence may be decreased with antiseptic procedures and hand hygiene. Antibiotic lock therapy is safe and effective. It is possible to obtain satisfactory results when ALT is used with intravenous systemic antibiotics for CRBSIs except in some cases catheter removal must be necessary. Antibiotic lock therapy helps to prevent unnecessary catheter removing in paediatric immunocompromised patients.